(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
Abstract The purpose of this study was to determine the implementation of the Savings and Loans Group Program in Improving. The type of research was qualitative and the data analysis used was descriptive qualitative. poor family. communication, socialization carried out by implementing actors has been carried out properly and monthly socialization by the manager to group administrators and group members. So that communication in the implementation of savings and loans (SPP) in all parties has gone well, Resources, in the selection of resources to be involved in savings and loan groups (SPP) have gone well. The disposition or attitude of the implementer is that the parties involved provide a good response to the implementer of the Savings and Loans (SPP) program which will later be able to achieve the objectives well. All the implementers involved have actually carried out their respective duties and responsibilities. There are two bureaucratic structures, namely the organizational structure and SOP (Operational Standards and Procedures) It has been running and well fulfilled, and the savings and loan managers, savings and loan group administrators and savings and loan members have fulfilled the bureaucratic structure. Keywords: Implementation, Savings and Loans Group Program